Cohesive Ties and Meaning Comprehension - Hamoudi, Ali Hindi (International Journal of Psychosocial Rehabilitation, 2020)
Cohesion is necessary in both spoken and written language. Speakers and writers use a variety of cohesive devices to link or clarify the relationships among ideas within a text or discourse. Cohesive devices are words used to show how the different parts of a text fit together to create cohesion. Cohesion is the grammatical and lexical linking within a text or sentence that holds a text together and gives it meaning. Hence, objective of this study is to reveal the significance of using such cohesive tools in grasping the meaning of a linguistic text through the analysis of the grammatical cohesive devices especially the personal references as cohesive ties in a short story written by a famous writer Ernest Hemingway entitled " Cat in the Rain" .The paper adopts a descriptive qualitative research method to identify the various personal references available in the above mentioned short story. The amount of occurrence and the category of anaphoric and cataphoric references are determined . This paper follows the model of cohesion set up by Halliday and Hasan in 1976 in Cohesion in English. The paper ends with some concluding remarks that are attained from the discussion of personal cohesive references in the selected text .